Ordering and transferring model of dual-channel supply chain with delivery time difference. (August 2021) - Xu, Fei; Wang, Honglei
Highlights: A model of order transferring co-operation strategy has been developed. The target inventory is affected by two factors. The existence of ordering Nash Equilibrium is obtained. The existence of stable interval has also been illustrated. Abstract: Customers with different delivery times in online and offline channels often lead to conflicts between two channels, which causes the loss of a large number of customers. Therefore, it is necessary to use the difference between the online and offline delivery to achieve the balance of inventory through order transferring. Aimed at this problem, a dual-channel supply chain system consisting of an online channel supplier and an offline retailer has been developed and sales stage has been expanded to two ones in order to explore the endogenous impact mechanism of different delivery periods on order transferring, and the structural properties of the order transferring threshold. Based on this, the optimal ordering strategy has been discussed at the beginning of the sales season by game theory. Secondly, the optimal threshold for order transferring of offline retailers in each stage by dynamic programming has been explored, and the relationship between the threshold and the sales stage has further been investigated in order to achieve a win-win co-operation by determining the optimal co-operative behavior. Finally, a numerical example has analyzed the influence of co-operation on ordering quantity, inventory quantity, and profit. Furthermore, we have also illustrated the existence of a stable interval when the delivery rate difference rate is lower, which simplifies the implementation of this strategy and improves its operability.